Stromal–epithelial interactions influence prostate cancer cell invasion by altering the balance of metallopeptidase expression - Dawson, L A (Nature Publishing Group, 2004)
Perturbations of stromal–epithelial interactions in the developing tumour can contribute to cancer invasion and metastasis. The structurally related metallopeptidases endothelin-converting enzyme (ECE) and neutral endopeptidase (NEP) contribute sequentially to the synthesis and inactivation of ET-1, a mitogenic peptide that has been shown to affect tumour behaviour. This study has investigated the interaction between metastatic tumour epithelial cells, which lack NEP, and stromal cells, which we have shown to express ECE-1 (stromal–epithelial interactions), using Matrigel invasion chambers. The epithelial cell lines utilised in this study include androgen-sensitive LNCaP, androgen-independent PC-3, Du145 and recently established PNT-1a, PNT2-C2 and P4E6 prostate cell lines. Specific inhibition of endogenous ECE-1 activity in stromal cells reduced PC-3 and Du145 invasion by 70 and 50%, respectively. Addition of recombinant NEP to inactivate endogenous mitogenic peptides resulted in 50 and 20% reductions in invasion in PC-3 and Du145 cells, respectively. Neutral endopeptidase effects were reversed in the presence of thiorphan, a specific NEP inhibitor. Supplementation of defined media with bradykinin and ET-1 significantly increased PC-3 invasion by 40 and 50%, respectively. Du145 cell invasion increased by approximately 100% on adding ET-1. These studies implicate the metallopeptidases NEP and ECE-1 as mediators of prostate cancer invasion via a stromal/epithelial interaction.